Protective effects of cornus mas extract on in vitro fertilization potential in methotrexate treated male mice - Zarei, Leila (Vet Res Forum, 2015)
Current study was aimed to evaluating protective effects of cornus mas fruit extract (CMFE) in mice treated with methotrexate (MTX). For this purpose, 48 young mature male mice were divided into 6 groups. Control group received only normal saline (0.1 mL per day, intraperitoneally), and the second group was administered MTX (20 mg kg(-1 )per week, intraperitoneally). The third, fourth and fifth groups received MTX daily oral doses of 250, 500 and 1000 mg kg(-1 )CMFE as well as MTX. The sixth group was only given CMFE with a dose of 1000 mg kg(-1 )per day, orally, for 35 days. Then, the animals were anesthetically euthanized and the sperms were separated from epididymis. DNA damage level, the amount of malondialdehyde (MDA) as well as in vitro fertility was evaluated. The number of sperms with damaged DNA and MDA level in MTX-treated group showed a significant increase compared to control group (p < 0.05). In groups receiving CMFE along with MTX, DNA damage level and MDA amount suggested a decrease in comparison with MTX group (p < 0.05). Also, in vitro fertilization and embryonic development in MTX-treated group was significantly lower than the control group, and the level of embryonic arresting was higher (p < 0.05). In groups which received CMFE along with MTX, in vitro fertility and embryonic development was higher than MTX group (p < 0.05) and the arrested embryos showed a decrease. This study suggested that cornus mas is able to ameliorate the side effects of MTX.